Preparation and characterization of lanthanum-based perovskite oxides LaMO3 (M=Fe, Cr, Mn) thin films by electrophoretic deposition - Raghad K Aljurays; Aicha Loucif; Mabrook S Amer; Abdullah M AlMayouf (Materials Research Express, 2023)
In this study, we report the fabrication and characterization of ${LaM}{O}_{3}$ $(M=Fe,Cr,Mn)$ perovskite thin films deposited on FTO substrates via electrophoretic deposition (EPD). The x-ray diffraction (XRD) patterns showed the formation of the orthorhombic structure for ${LaFe}{O}_{3}$ and ${LaCr}{O}_{3}$ films and the trigonal structure for the ${LaMn}{O}_{3}$ film. The field-emission scanning electron microscopy (FE-SEM) micrographs revealed nano-spherical particles with an average grain size of about 50 nm covering the ${LaMn}{O}_{3}$ surface with fewer porosities compared to the other films. Moreover, the ${LaMn}{O}_{3}$ film exhibited a higher transparency in the visible region (∼84%). The estimated bandgaps of ${LaFe}{O}_{3},$ ${LaCr}{O}_{3},$ and ${LaMn}{O}_{3}$ perovskite films were found to be 2.17, 3.18, and 2.92 eV, respectively. In addition, the refractive indices of all deposited films were calculated using five empirical models that relate the refractive index to the bandgap, which consistently revealed a decrease in refractive index with an increase of bandgap energy This study holds significant implications for the field of perovskite thin films as we contribute new insights into the fabrication of lanthanum-based perovskite thin films using the EPD technique. The comprehensive characterization of microstructural, morphological, and optical properties provides valuable information for understanding the structure-property relationship in these materials. Furthermore, the determination of bandgaps and refractive indices enhances our understanding of the optical properties of perovskite films. The findings from this study pave the way for potential applications in optoelectronic devices, where fine-tuning of material properties is critical for optimal device performance.